Answer:
![3\sqrt[4]{5}](https://tex.z-dn.net/?f=3%5Csqrt%5B4%5D%7B5%7D)
Step-by-step explanation:
Given: ![\frac{\sqrt[4]{810} }{\sqrt[4]{2} }](https://tex.z-dn.net/?f=%5Cfrac%7B%5Csqrt%5B4%5D%7B810%7D%20%7D%7B%5Csqrt%5B4%5D%7B2%7D%20%7D)
Top and bottom has fourth root. so we take fourth root in common
![\sqrt[4]{\frac{810}{2} }](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B%5Cfrac%7B810%7D%7B2%7D%20%7D)
When we divide 810 by 2. we will get 405
![\sqrt[4]{405}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B405%7D)
Now we simplify the fourth root
405 can be written as 3*3*3*3*5
![\sqrt[4]{3*3*3*3*5}](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B3%2A3%2A3%2A3%2A5%7D)
![3\sqrt[4]{5}](https://tex.z-dn.net/?f=3%5Csqrt%5B4%5D%7B5%7D)
Answer:
40√3
Step-by-step explanation:
(4√2)(5√6) = 40√3
Answer: a and b
Step-by-step explanation:
Answer:
Step-by-step explanation:
The Pascal triangle is used to determine the coefficients of the terms when we expand the expression.
1
= 1
1 1 ![(A +B ) ^ 1 = 1A + 1B](https://tex.z-dn.net/?f=%28A%20%2BB%20%29%20%5E%201%20%3D%201A%20%2B%201B)
1 2 1 ![(A+ B) ^ 2 = 1A^2 + 2 AB + 1B^2](https://tex.z-dn.net/?f=%28A%2B%20B%29%20%5E%202%20%3D%201A%5E2%20%2B%202%20AB%20%2B%201B%5E2)
By extending the triangle, you will get the 9th row, which is your expression, of the coefficients. that is
1 9 36 84 126 126 84 36 9 1
Now, fill in AB in the gaps.
1AB + 9 AB + 36AB + 84AB + 126AB + 126AB +84AB + 36AB + 9AB + 1AB
Next, you need to go from the left to fill out the exponent of A and it will go down from 9 (the exponent of the whole thing) . That is
![1A^9B+9A^8B+36A^7B+84A^6B+126A^5B+126A^4B+84A^3B+36A^2B+9A^1B+1A^0B](https://tex.z-dn.net/?f=1A%5E9B%2B9A%5E8B%2B36A%5E7B%2B84A%5E6B%2B126A%5E5B%2B126A%5E4B%2B84A%5E3B%2B36A%5E2B%2B9A%5E1B%2B1A%5E0B)
Next will be the exponent of B. this time, you go from the right and do the same with A. You can go from the left also, but go up from 0 to 9 for the exponent of B
![1A^9B^0+9A^8B^1+36A^7B^2+84A^6B^3+126A^5B^4+126A^4B^5+84A^3B^6+36A^2B^7+9A^1B^8+1A^0B^9](https://tex.z-dn.net/?f=1A%5E9B%5E0%2B9A%5E8B%5E1%2B36A%5E7B%5E2%2B84A%5E6B%5E3%2B126A%5E5B%5E4%2B126A%5E4B%5E5%2B84A%5E3B%5E6%2B36A%5E2B%5E7%2B9A%5E1B%5E8%2B1A%5E0B%5E9)
The last step is just to simplify the A^0=1 and B^0 =1 at the first and the last terms.
![A^9+9A^8B^1+36A^7B^2+84A^6B^3+126A^5B^4+126A^4B^5+84A^3B^6+36A^2B^7+9A^1B^8+B^9](https://tex.z-dn.net/?f=A%5E9%2B9A%5E8B%5E1%2B36A%5E7B%5E2%2B84A%5E6B%5E3%2B126A%5E5B%5E4%2B126A%5E4B%5E5%2B84A%5E3B%5E6%2B36A%5E2B%5E7%2B9A%5E1B%5E8%2BB%5E9)
Hope you can learn the method
Answer:
Below in bold.
Step-by-step explanation:
Amount originally in the cup = amount she drank + amount remaining
= 17 * 4.5 + 148.5
= 76.5 + 148.5
= 225 milliliters.
The time she takes to drink the 148.5 mL = 148.5 / 4.5
= 33 seconds.
So time to drink it all = 17 +33 = 50 seconds.